World Class Operation Exploration – Honeywell H.O.S and V.P.D - Cai, Tian (2009)
This project focuses on strategy, world class operation theory, investigate world class operation practice in Business represented by V.P.D and H.O.S and explore how it help the firm excal in present competitive context and continue the thrust in long run.